High hydroxide conductivity in a chemically stable crystalline metal-organic framework containing a water-hydroxide supramolecular chain - Nagarkar, Sanjog S.; Anothumakkool, Bihag; Desai, Aamod V.; Shirolkar, Mandar M.; Kurungot, Sreekumar; Ghosh, Sujit K. (Chemical Communications, 2016)
A chemically stable cationic MOF encapsulating an in situ formed water-hydroxide supramolecular anionic chain is realized for high hydroxide (OH-) ion conductivity in the solid-state (Type A). High OH- ion conductivity and low activation energy of the MOF demonstrate the advantage of the in situ incorporation of OH- ions to achieve efficient OH- ion conduction in the solid-state.